THE EXISTENCE OF TUTORS IN CARRYING OUT NON-FORMAL EDUCATION SERVICES AT SKBN 2 SAMARINDA: EKSISTENSI TUTOR DALAM MELAKSANAKAN LAYANAN PENDIDIKAN NONFORMAL DI SKBN 2 SAMARINDA - Meydina Fauziah Putri; Arif Sugianto; Sri Wahyuni; Hepy Triwinarti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to examine the role of tutors in implementing non-formal education services at SPNF SKB Negeri 2 Samarinda with a focus on the role of tutors as facilitators, motivators, evaluators and social companions. This study uses a qualitative approach. The data collection techniques used are interviews, observations, and documentation studies.Data analysis techniques include the data condensation stage, data presentation (matrix/theme network), as well as conclusion drawing and verification, coding is carried out deductive-inductive (initial code from role theory concepts, andragogy principles, competency development enriched through open coding to saturation). The results of the study show that tutors at SPNF SKB Negeri 2 Samarinda play an important role in creating a participatory and relevant learning atmosphere that is in accordance with the principles of andragogy. As motivators, tutors provide psychological support and enthusiasm to residents to learn with a personal approach. As evaluators, they conduct assessments based on contextual understanding and provide constructive feedback. On the other hand, as social companions, tutors pay attention to the personal condition of learning residents to create social bonds that strengthen the sustainability of the learning process. While there is already recognition of the existence of tutors, the study also found a need to strengthen the professional capacity of tutors through relevant training and rewards equivalent to their contributions. For this reason, non-formal educational institutions need to provide more support in the form of continuous training, formal recognition and fair performance evaluations so that tutors can carry out their roles optimally.